Rancang Bangun Sistem Informasi Inventori Barang Masuk dan Keluar pada Bengkel Aries Star Motor Berbasis Websiste - Fabianus Once Renggi; Kristianus Jago Tute; L.B Finansius Mando (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
The problem that occurs in this study is the Aries Star Motor workshop which is engaged in the supply of automotive goods as a place to renovate a two-wheeled vehicle, this workshop has a lot of vehicle parts that are stored and not recorded properly and are still manual by using books. and calculators, be it transactions or reports so as to make workshop performance less effective and efficient. Employees sometimes still cannot distinguish the names of goods and the code of goods. Of course this problem will make financial reports and inventory reports will not be well controlled. The purpose of this research is to design an inventory information system for incoming and outgoing goods at a website-based Aries star motor workshop. The method used in this study is a descriptive qualitative method with a qualitative approach with data collection techniques in the form of observations, interviews, and literature studies. System development using the waterfall method and testing using black box testing the results of the system made are able to design an inventory information system for incoming and outgoing goods properly and can be implemented. The conclusion is that it can implement the design of the incoming and outgoing goods inventory information system at the website-based Aries star motor workshop so that it is better.